2018
DOI: 10.3389/fnmol.2018.00365
|View full text |Cite
|
Sign up to set email alerts
|

Shank2 Mutant Mice Display Hyperactivity Insensitive to Methylphenidate and Reduced Flexibility in Social Motivation, but Normal Social Recognition

Abstract: Mouse models of autism can be used to study evolutionarily conserved mechanisms underlying behavioral abnormalities in social communication and repetitive behaviors. SHANK genes code for synaptic scaffolding proteins at excitatory synapses and mutations in all SHANK genes have been associated with autism. Here, we present three behavioral aspects of the mutant mice deleted for exon 16 in Shank2. First, we treated Shank2 mutant mice with methylphenidate to rescue the hyperactivity. Our failure to do so suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…Lastly, we found that Shank2 −/− mice were hyperactive during habituation, which is in line with published reports using similar mutants 56‐59 . However, visual discrimination acquisition and reversal learning were not significantly different in Shank2 −/− mice and their WT littermates.…”
Section: Discussionsupporting
confidence: 92%
“…Lastly, we found that Shank2 −/− mice were hyperactive during habituation, which is in line with published reports using similar mutants 56‐59 . However, visual discrimination acquisition and reversal learning were not significantly different in Shank2 −/− mice and their WT littermates.…”
Section: Discussionsupporting
confidence: 92%
“…The emission of a large number of spontaneous USVs suggests that female mice are sufficiently aroused in their normal "home-cage-like" life. In short-term experiments, socially-housed mice never reach this level of excitement during the first minutes of interaction and therefore emit few USVs (e.g., (Ey et al, 2018;Hammerschmidt et al, 2012)). The emission of a large quantity of USVs can only be reached by social deprivation over such short periods.…”
Section: Hypotheses About the Functions Of Usvsmentioning
confidence: 99%
“…During development, mouse pups isolated from the dam and littermates emit USVs as distress calls that trigger approach and retrieval by the mother (Sewell, 1970;Zippelius and Schleidt, 1956). In juveniles and adults, socially-deprived mice are highly motivated to interact with conspecifics; this maximizes the quantity of USVs emitted, which may be used to regulate close contacts and hierarchy (Ey et al, 2018;Moles et al, 2007). Finally, an estrous female, or at least its odor, stimulates adult males to vocalize (Chabout et al, 2015;Holy and Guo, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In Ndrg2 de cient mice, their ADHD-like hyperactivity was not rescued by MPH [46]. Shank2 and Fmr1 mutant mice, both are the model of autism, display hyperactivity, but the injection of MPH increased their locomotion activity [47,48]. Relevant to the effect of MPH in Shank2 and Fmr1 de cient mice, hyperactivity in Trpm1 de cient mice may not be related to ADHD, but instead autism which is also one of the phenotypes in 15q13.3 microdeletion syndrome (Table S1) [5,49].…”
Section: Discussionmentioning
confidence: 98%